Obstáculos que impiden el acercamiento entre los Estados Unidos y Cuba - González, Edward (Estudios Internacionales, 1994)
Right now, the fall of communism, the disappearance of the Soviet Union and the consequent crisis in Cuba, apparently could give way to a possible rapprochement between Washington and Havana. However, the resolution of the conflict between the two does not seem imminent. What explains the paralysis of both parties when the world, Cuba and the United States have changed? In this paper, we argue that both new and old "contradictory" interests continue to fundamentally separate the two governments, presenting greater obstacles to normalization. In this sense, and paradoxically, the Cuban crisis, which is growing, constitutes another impediment to the solution of the conflict on both sides of the Florida Strait. Finally, we conclude with a few remarks regarding US policy options.